Bridging the gender gap: women in fisheries industry policy on the North Coast of West Java, indonesia - Indriasih, Dewi; Mulyantini, Sri; Fajri, Aminul; Rimbawan, Teguh (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The purpose of the study is to examine the model of women's empowerment in creating financial independence. The research method uses a qualitative descriptive approach, data collection is carried out through in-depth interviews with relevant stakeholders, namely women's mobilization shops in fishing villages in 11 sub-districts and 32 villages in Indramayu, Manpower Office, Fisheries and Marine Service, Social Service, Environment Office. Data analysis using the help of Nvivo 12 Plus software for visualization and mapping data conclusions. The result of this study is the strategy of empowering women in creating financial independence, showing that the empowerment of women in fishing villages in North Coast, West Java uses a partnership strategy. The research result that awareness and socialization were carried out by village cadres who had been trained by several agencies. The government agencies that appointed to carried out several empowerments program for women's groups, namely by the Manpower Agency, Fisheries and Marine Agency, Social Service Agency, Environmental Affairs Agency with utilizing the potential of local resources. Strategies to increase the capacity of women empowerment are carried out training and mentoring around financial and business literacy and strengthening social capital, as well as environmental awareness.